Kritik Sastra Objektif Terhadap Puisi Dalam Do’a Ku Karya Sapardi Djoko Damono - Widianti, Agustina; Dwi Astuti , Roro (Jurnal Multidisiplin Indonesia, 2023)
Poetry is a literary work that contains a lot of meaning and meaning in each stanza. In this research, researchers studied the poem Dalam Doaku using an objective approach. An objective approach was taken to examine more deeply the content of the poem In My Prayer. This approach examines the physical structure and inner structure of the poem. This research was conducted using descriptive qualitative research methods. In the poem "In my prayer" by Sapardi Djoko Damono, it is found that there are inner structures such as typography, diction, imagery, rhyme, language style and concrete words. Meanwhile, in the inner structure, themes, tone, feelings and also messages are found.